1978
DOI: 10.1016/s0022-5347(17)57390-5
|View full text |Cite
|
Sign up to set email alerts
|

Pubovaginal Sling Procedure for Stress Incontinence

Abstract: Urinary stress incontinence associated with poor urethral sphincter function and indicated by a urethral pressure of less than 10 cm. water was treated in 52 cases with a pubovaginal autogenous fascial sling. No urethral sphincter function could be measured in 7 patients. Of these 52 patients 42 had undergone a previous operation for stress incontinence. The uninhibited detrusor dysfunction that accompanied the stress incontinence in 29 cases ceased after operation in 20 but persisted in 9. Postoperative ureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(95 citation statements)
references
References 3 publications
1
91
1
2
Order By: Relevance
“…4 After several modifications were reported in the years that followed, it was McGuire and Lytton who popularized the procedure in 1978. 5 In 1988, Blavais and Olson placed emphasis on positioning the sling at the bladder neck level in an effort to correct urethral hypermobility. 6 Delancey proposed his "hammock hypothesis" in 1994, which has further contributed to the understanding of how a sling functions to compress the urethra with increased intra-abdominal pressure when placed at the bladder neck.…”
Section: Introductionmentioning
confidence: 99%
“…4 After several modifications were reported in the years that followed, it was McGuire and Lytton who popularized the procedure in 1978. 5 In 1988, Blavais and Olson placed emphasis on positioning the sling at the bladder neck level in an effort to correct urethral hypermobility. 6 Delancey proposed his "hammock hypothesis" in 1994, which has further contributed to the understanding of how a sling functions to compress the urethra with increased intra-abdominal pressure when placed at the bladder neck.…”
Section: Introductionmentioning
confidence: 99%
“…Previously PVT and similar sling surgeries were recommended, especially for type III SUI. But recently, the success of sling applications have changed the algorithm, and become the 'Gold Standart' treatment option for all SUI cases, regardless of the sub group [11][12][13]. Different studies have reported success rates of PVT, and similar loose suspension surgeries between 75-100%, making PVT and similar sling surgeries the perfect treatment alternatives for stress urinary incontinence with these results [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In these women with low urethral closure pressures good results have been achieved after fascial sling procedures. 15 Therefore sling procedures may be the treatment of choice for those with preoperative evidence of poor urethral sphincter function. Women with hypermobility and coexistent ISD will benefit from a sling procedure, even if hypermobility is the only clinical feature, because the sling will correct the ISD that these women have.…”
Section: Indications and Benefitsmentioning
confidence: 99%